SARS-CoV-2 Antibody Responses Do Not Predict COVID-19 Disease Severity. Issue 4 (15th July 2020) - Phipps, William S; SoRelle, Jeffrey A; Li, Quan-Zhen; Mahimainathan, Lenin; Araj, Ellen; Markantonis, John; Lacelle, Chantale; Balani, Jyoti; Parikh, Hiren; Solow, E Blair; Karp, David R; Sarode, Ravi; et al.
Abstract: Objectives: Initial reports indicate adequate performance of some serology-based severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) assays. However, additional studies are required to facilitate interpretation of results, including how antibody levels impact immunity and disease course. Methods: A total of 967 subjects were tested for IgG antibodies reactive to SARS-CoV-2, including 172 suspected cases of SARS-CoV-2, 656 plasma samples from healthy donors, 49 sera from patients with rheumatic disease, and 90 specimens from individuals positive for polymerase chain reaction (PCR)–based respiratory viral panel. A subgroup of SARS-CoV-2 PCR-positive cases was tested for IgM antibodies by proteome array method. Results: All specificity and cross-reactivity specimens were negative for SARS-CoV-2 IgG antibodies (0/795, 0%). Positive agreement of IgG with PCR was 83% of samples confirmed to be more than 14 days from symptom onset, with less than 100% sensitivity attributable to a case with severe immunosuppression. Virus-specific IgM was positive in a higher proportion of cases less than 3 days from symptom onset. No association was observed between mild and severe disease course with respect to IgG and IgM levels. Conclusions: The studied SARS-CoV-2 IgG assay had 100% specificity and no adverse cross-reactivity. Measures of IgG and IgM antibodies did not predict disease severity in our patient population.